Clinical and functional outcome of traumatic osteochondral fracture in adolescent patella - Aziz, Sobia; Khan, Noman; Dina, Twahir Kalekhan; Sufyan, Muhammad; Kazim, Muhammad; Zaheer, Arisha (Journal of the Pakistan Medical Association, 2024)
The objective of this descriptive cross-sectional study was to assess the functional outcomes of adolescents who had undergone internal fixation for patellar post-traumatic OCD fracture from 2019-2021. The injury mechanism was divided into two categories: a) torsional mechanism and b) direct contact injury. All candidates underwent X-ray and MRI/CT scan prior to the surgery to confirm the diagnosis. Operative treatment was open reduction and internal fixation (ORIF) of osteochondral fragment using headless screws. All patients were assessed pre-operatively with knee-ROM/IKDC (International Knee Documentation committee) score and satisfaction score, and post-operatively at one year follow-up. Fourteen patients were selected, with the mean age of 16.1±3.2 years. On one-year follow-up, no difference was noted in ROM when compared to the unaffected limb. The mean satisfaction score was 86±6.3 %. The mean pre-operative-IKDC score was 47.6±5.8 out of 100, whereas on one-year follow-up it was 88.6±2.2 which was statistically significant (p-value <0.05). ---Continue